Peningkatan Kinerja Guru Dalam Menyusun Perangkat Pembelajaran Melalui Supervisi Akademis - Handoko, Hanwar Priyo (Jurnal Dewantara, 2017)
The performance of teachers in planning lessons significantly increased through the optimization of academic supervision by the engineering group and individually. It is based on the findings: 1) Improvement of documents going from 50%, 88% and 94%. PTS proposed to increase by 90%, thus an indicator of success in the documents has been reached and the cycle is stopped; 2) The four pred-belt performance appraisals in the first cycle, the distribution of the predicate is: Not good enough 0%, 42% fairly well, 58% good and very good 0%. In the second cycle, the distribution of the predicate is: Not good enough 0%, good enough 8, both 42% and excellent 49. Predicate Good and Very Good is 42 + 49 = 91%. Thus, it can be said an increasing number of distribution Prasiklus to cycle performance category I.